ANALYSIS OF SUPPLY CHAIN NETWORK BY RULES OF ORIGIN IN FTA ENVIRONMENT - Byun, Taesang; Oh, Jisoo; Jeong, Bongju (International Journal of Industrial Engineering: Theory, Applications and Practice, 2014)
This paper presents a supply chain in Free Trade Agreements (FTA) environments governed by rules of origin and analyzes it using profit analysis and supply chain planning. The proposed supply chains follow the rules of origin as wholly obtained, substantially transformation, and third country processing criteria. All of these supply chain can be used to take non-tariff benefits according to the rules of origin. In order to evaluate the validity of the proposed supply chain, we construct profit models and show optimal sales prices can maximize net profits. The profit model encompasses the structure of supply chain which enables decision-makers to make a strategic decision on evaluation and selection of efficient FTA. Using the output of profit models, global supply chain planning models are built to maximize profit and customer needs. A case study for a textile company in Korea is provided for illustrating how the proposed supply chain models work.